Implementation Process of Project Control Systems and Performance of Rural Roads Construction Projects in Kenya: Role of Project Team Experience Diversity - Josiah Obiria Obare; Dorothy Ndunge Kyalo; Angeline Sabina Mulwa; John Mbugua (European Scientific Journal, ESJ, 2016)
Project managers have always endeavoured to effectively implement project controls systems during execution of projects to enhance rates of projects successes. However lack of understanding of the role of diversity of experiences among the workforce has hindered the ultimate performance of the project control systems in influencing the performance of construction projects. This paper sought to establish the extent to which project team experience diversity influence on the relationship between implementation process of project control systems and performance of rural roads construction projects in Kenya. The study adopted the pragmatism paradigm and the correlational survey research design. Descriptive statistics were analysed using frequencies, percentages, arithmetic mean and standard deviation while inferential statistics were analysed using Pearson’s Product Moment correlation (r), simple regression and stepwise regression (R2). Ftest was used to test the hypotheses. Tests of statistical assumptions were carried out before analysis. The results indicated that with r= 0.533, R2 = 0.284 F (1,195) = 77.208 at p=0.0000.05, the null hypothesis was failed to be rejected and therefore concluded that the significant relationship between implementation process of project control systems and performance of rural roads project does not depend on the interaction between implementation process of project control systems and project team experience diversity. It was therefore recommended that project team experience diversity among the professionals should be encouraged, communicated and shared for the common purpose of achieving high performance in projects.